Occurrence of Aflatoxin M1 in Raw Milk in Trakya Region, Turkey - Ozsunar, A.; Gumus, T.; Arici, M.; Demirci, M. (Asian Journal of Chemistry, 2010)
The occurrence of aflatoxin M1 (AFM1) was investigated in raw cow's milk samples using an ELISA method (Ridascreen). The lower detection limit of AFM1 test was 0.005 μg/L. The presence of AFM1 in 90 samples of raw milk obtained at March and June 2005 from a dairy plant and 45 samples collected randomly at June 2005 in Trakya region of Turkey were analyzed. In all of the samples obtained in March the presence of aflatoxin M1 was detected in concentrations ranging between 0.0077 and 0.0683 μg/L. Aflatoxin M1 level in only one of positive samples was higher than the maximum tolerance limit (0.05 μg/L) accepted by Turkey and European Union countries. Incidence level of AFM1 in month of March was higher than the month of June samples. Statistical evaluations showed that mean contamination level of AFM1 in March samples were significantly higher (p < 0.01) than June. In addition the results showed that there were no statistical differences between AFM1 contents of March and June samples.